The Implementation of Board Games in Teaching Speaking for Tenth Graders in Senior High School - Dewi, Hetty Amala (RETAIN, 2021)
Abstract The ability to speak is one of the aspects which are very important to communicate and the ability to be taught in the classroom. Unfortunately, mastering speaking skills for students who learn a foreign language that is English is not easy. In fact, there are many students are afraid of speaking English when studying in class. Thus, the teacher should teach using an acceptable media. An easy medium capable to promote students’ speaking capacity is a board game. However, the points of this study are to describe how the board game can be used in the process of learning English especially speaking descriptive texts, and to find out how students’ respond to their use in the learning process. However, the points of this study are to describe how the board game can be used in the process of learning English especially speaking descriptive texts, and to find out how students’ respond to their use in the learning process. The researcher used qualitative research. Observation checklist, field note, and the result of the questionnaire were used in the injunction to find the data required for this research. This study was conducted at SMAN 1 Sumenep. The participant for this study were an English teacher and twenty-nine (29) students of X IPA3 class with different speaking skills to be the subjects of this research. The result of this study is boardgame gave an encouraging impact on the increase students’ speaking proficiency. It was substantiated by the students’ opinion in the questionnaire that uses of boardgame could motivate and attract students’ interest so students can be brave in speaking descriptive text. The use of board games also could make the students more aware of the teacher’s explanation in learning process, also could make the students relaxed in class. In conclusion, implementing a board game as a medium to teach speaking descriptive text was very useful for the teacher and stimulating media for students to increase their speaking ability especially in descriptive text. Keywords: Speaking, Descriptive Text, Boardgame